Transzendentalität und Realität - Schnell, Alexander (2014)
Transcendentality and Reality From a phenomenological point of view the 'real' is neither to be identified with the 'given' nor with the 'withdrawn'. It rather has to be examined in its relatedness to the factual. This in turn requires the reflection of the basic correlation of being and thought. By engaging in this task the author of this essay distinguishes five modalities: 1. the possibility of the accessibility of the world, 2. the actual modes of constitution of appearance 3. the genetic moment of phenomenalization, 4. The eventfulness and singularity of every case, 5. the existence of the world as such. These modalities constitute the realm of the transcendental and they allow us to differentiate how the real 'exists'. In this sense the essay continues the work of Richir's " phenomenology of the real " , at the same time it goes beyond Richir's work. The standpoint of " phenomenological constructivism " allows the integration of skepticist insights into the concept of the transcendental.